2014
DOI: 10.1245/s10434-014-4278-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Rectal Cancer Resection: A Retrospective Multicenter Analysis

Abstract: Robotic-assisted minimally invasive surgery for the treatment of rectal cancer is safe and can be performed according to current oncologic principles. BMI seems to play a minor role in influencing outcomes. Thus, robotics might be an excellent treatment option for the challenging patient undergoing resection for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…Several retrospective studies have indicated that robotically assisted colectomy is a safe option in the treatment of colorectal cancer; at least one prospective study is expected to confirm this finding in rectal cancer. [7, 8] However, data comparing incisional hernia rate and other wound complications in patients treated with laparoscopic or robotic colectomy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have indicated that robotically assisted colectomy is a safe option in the treatment of colorectal cancer; at least one prospective study is expected to confirm this finding in rectal cancer. [7, 8] However, data comparing incisional hernia rate and other wound complications in patients treated with laparoscopic or robotic colectomy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Overall operative time was included in the majority of studies and was the only reported outcome that was associated with obesity in a majority of publications (Table ) . Among the 70 studies that included operative time as an outcome metric, 42 (60%) reported that obesity was associated with a longer operative time …”
Section: Resultsmentioning
confidence: 99%
“…A subset analysis was performed that examined SSI data among patients with colorectal cancer relative to surgical approach. Among the 54 studies on colorectal cancer, 16 included data on minimally invasive techniques . Among these 16 studies, 3 did not evaluate SSI .…”
Section: Resultsmentioning
confidence: 99%
“…Ultra-low resections also had longer operative times. The authors concluded that BMI seemed to play a minor role in influencing outcomes (65).…”
Section: Robotic Colorectal Surgerymentioning
confidence: 99%